Hot work die steel, heat treatment method thereof and hot work die
Patent Information
- Application Number
- CN202380048848.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-21
- Filing Date
- 2023-01-06
- Publication Date
- 2025-02-18
AI Technical Summary
The thermal conductivity of existing hot work die steel decreases at high temperatures, resulting in thermal fatigue and reduced wear resistance, making it difficult to achieve performance matching of high thermal conductivity, high hardness, and high toughness at the same time.
By properly proportioning Ni, Al and Cu elements, NiAl intermetallic compounds and Cu particles are formed to ensure that these alloy elements are completely precipitated after hardening treatment, improving thermal conductivity and hardness, and by coordinating Cu content and hardening temperature to avoid precipitation phases of coarsening.
The high hardness, high thermal conductivity and high toughness of hot work die steel are achieved, extending the service life, simplifying the heat treatment process and reducing costs.
Smart Images

Figure CN119487231A_ABST
Abstract
Description
Hot working die steel, heat treatment method thereof and hot working die Technical Field
[0001] The invention relates to hot working die steel, a heat treatment method thereof and a hot working die. Background Art
[0002] Hot work die steel is an alloy tool steel made by selectively adding varying weight percentages of alloying elements such as carbon, silicon, chromium, tungsten, molybdenum, nickel, manganese, vanadium, and cobalt to iron. It is often used to form dies for forming materials during die casting, forging, and extrusion. In recent years, hot stamping technology—a forming technology for advanced high-strength automotive steel sheets that simultaneously meets vehicle lightweighting and safety requirements—has placed new demands and challenges on die steel.
[0003] The thermal conductivity of commonly used hot work die steel at room temperature is 18 to 24 W / mK. Generally speaking, above a certain temperature, thermal conductivity decreases with increasing temperature. During service, hot work dies are often subjected to high thermomechanical loads at high temperatures, which can lead to thermal shock or thermal fatigue caused by thermal gradients. On the one hand, high temperatures can reduce the thermal conductivity of hot work dies, and the thermal expansion differences caused by temperature differences in the materials can cause thermal fatigue cracks in the hot work dies, shortening the service life of the hot work dies. On the other hand, at high temperatures, the hardness of the precipitated carbides that ensure the wear resistance of the hot work dies decreases, resulting in low wear resistance of the hot work dies at high temperatures.
[0004] It's well known that higher a material's thermal conductivity leads to lower thermal gradients, resulting in lower surface loads on the material, less thermal shock and thermal fatigue, and thus a longer service life. Therefore, hot work tool steels with high thermal conductivity, high hardness, and high toughness are desirable to enhance the tool's resistance to thermal cracking and wear, thereby extending its service life. Furthermore, the tool's high thermal conductivity accelerates cooling during production, shortening cycle times.
[0005] US Pat. No. 9,689,061 B2 discloses a high thermal conductivity alloy tool steel. Its alloy composition, by weight, is as follows: C: 0.26-0.55%, Cr: <2%, Mo: 0-10%, W: 0-15%, Mo+W: 1.8-15%, Ti+Zr+Hf+Nb+Ta: 0-3%, V: 0-4%, Co: 0-6%, Si: 0-1.6%, Mn: 0-2%, Ni: 0-2.99%, S: 0-1%, with the remainder being Fe and unavoidable impurities. The patent teaches that after solution treatment and hardening, Mo and W carbides replace Cr carbides, thereby improving the thermal conductivity of the alloy tool steel. However, the size of the Mo and W carbides is difficult to control, particularly the size of the undissolved primary carbides after solution treatment, which is approximately 3 μm. These large carbides will become the source of fatigue cracks, which will not only seriously affect the fatigue life of the tool steel, but also seriously deteriorate its toughness. Domestic researchers have found that although the thermal conductivity of this high thermal conductivity alloy tool steel is ~47W / mK at room temperature, its thermal conductivity coefficient decreases with increasing temperature. At 300°C, its thermal conductivity is less than 39W / mK, and when the temperature reaches 500°C, its maximum thermal coefficient is only 35W / mK. Moreover, when the hardness value reaches 50HRC or above, the impact energy (7×10mm unnotched specimen) is less than 210J. When this high thermal conductivity alloy tool steel is used at high temperatures, it loses its advantage of high thermal conductivity and fails to achieve a good performance match of high thermal conductivity, high toughness and high hardness.
[0006] CN 108085587 A provides a high-temperature, long-life hot die steel for die casting with excellent thermal conductivity and a manufacturing method thereof. The chemical composition of this high-thermal-conductivity, long-life hot die steel for die casting, by weight, is as follows: C: 0.35-0.45%, Si: 0.20-0.30%, Mn: 0.30-0.40%, Ni: 0.50-1.20%, Cr: 1.5-2.2%, Mo: 2-2.6%, W: 0.0001-1.0%, Ti: 0-0.40%, V: 0.30-0.50%, B: 0.0001-0.003%, Cu: 0.005-0.02%, with the remainder being Fe and unavoidable impurities. This patent also utilizes Mo and W carbides in place of Cr carbides. However, the following problems exist: 1) Carbide size is difficult to control, and oversized carbides degrade toughness; 2) Adding Ti easily forms liquid TiN and oversized TiC, which degrades toughness; 3) Cr cannot completely precipitate from the matrix as carbides, making high thermal conductivity impossible to achieve; 4) Multiple tempering processes are cumbersome and require avoiding secondary hardening peaks, otherwise the material will have the highest hardness but the lowest toughness. In the preferred embodiment of this patent, the U-shaped impact test of the example steel showed an impact energy of no more than 50 J and a maximum thermal conductivity of 35.982 W / mK, failing to achieve a good performance match of high thermal conductivity, high toughness, and high hardness.
[0007] CN104046917B provides an ultra-high-strength ferrite steel reinforced with nano-intermetallic compounds. The chemical composition of the ultra-high-strength ferrite steel is as follows by weight: C: 0-0.2%, Cu: 0.5-5%, Ni: 0.01-4%, Mn: 0.01-4%, Al: 0.001-2%, Cr: 0-12%, Mo: 0-3%, W: 0-3%, Mo+W not less than 0.05%, V: 0-0.5%, Ti: 0-0.5%, Nb: 0-0.5%, V+Ti+Nb not less than 0.01%, Si 0-1%, B: 0.0005-0.05%, P not more than 0.04%, S not more than 0.04%, N not more than 0.04%, O not more than 0.05%, and the balance is Fe and unavoidable impurities. This patent teaches that after rolling, steel is subjected to solid solution and aging treatment, and can be made into ferritic steel based on nano-metallic compound strengthening and combined with fine grain, solid solution and dislocation strengthening, to obtain excellent toughness, weldability and corrosion resistance. However, because the alloying elements are still mostly solid-dissolved in the ferrite matrix after the final heat treatment, the thermal conductivity of ultra-high strength ferritic steel is low. For example, Cr is solid-dissolved in the ferrite matrix and forms Cr carbides, which not only have low thermal conductivity, but also easily coarsen during heat treatment, worsening the toughness of the material. For example, Si, Cr and Al elements, when they are solid-dissolved in the ferrite, can seriously reduce the thermal conductivity of ferrite. In addition, the carbonitrides of the microalloying elements V, Ti and Nb not only reduce the thermal conductivity of steel, but also reduce the toughness of steel.
[0008] CN105568151B provides an aluminum-reinforced martensitic steel, the chemical composition of which is, by weight percentage, the following: C: 0.01-0.2%, Ni: 6-24%, Mo: ≤6%, Mn: 0-4%, Al: 0.5-6%, Cr: 0-12%, Nb: ≤1.5%, Cu: 0-4%, W: 0-3%, B: 0.0005-0.05%, with the remainder being Fe and unavoidable impurities. This patent removes Ti and Co and designs an alloy system that is primarily strengthened with NiAl, combined with trace carbides and nanoclusters of Cu for co-strengthening. This results in an aluminum-reinforced martensitic steel with a strength greater than 2000 MPa, an elongation greater than 6%, and excellent fatigue and processing properties. However, this patent fails to rationally balance Ni, Al, and Cu, resulting in excess Al being dissolved in the matrix, causing a serious decrease in the thermal conductivity of the matrix.
[0009] CN111636037A provides a hot work die steel whose chemical composition, by weight, is as follows: Cu: 2-8%, Ni: 0.8-6%, with Ni:Cu ≥ 0.4, C: 0-0.2%, Mo: 0-3%, W: 0-3%, Nb: 0-0.2%, Mn: 0-0.8%, Cr: 0-1%, Al: 0-3%, with Ni:Al ≥ 2 (preferably 2-2.5), the remainder being Fe and unavoidable impurities. This patent utilizes a large amount of Cu precipitates, supplemented by NiAl precipitates and carbides as strengthening phases to increase the hardness of the hot work die steel. Furthermore, the thermal conductivity of the matrix is enhanced primarily by the precipitation of a large number of Cu particles from the matrix. After solution treatment and aging treatment, the hot work die steel exhibits the following properties: hardness ≥ 42 HRC, thermal conductivity ≥ 35 W / mK, and room temperature impact energy ≥ 250 J for an unnotched 7×10 mm specimen. However, this patent fails to recognize the effect of Al solid solution in the matrix on thermal conductivity, and therefore cannot further improve the thermal conductivity of hot working die steel.
[0010] CN110578103B provides a plastic mold steel with high toughness, high polishability, and high corrosion resistance. By adding Cu and Al to the plastic mold steel, this patent significantly improves its surface polishing and corrosion resistance, significantly extending its service life. On the one hand, the plastic mold steel does not need and cannot meet the performance requirements of hot work mold steel. On the other hand, although Cu, Ni, and Al are added, they are not properly proportioned, resulting in no significant improvement in thermal conductivity. Furthermore, other elements such as Si, Cr, and V significantly reduce thermal conductivity, resulting in the plastic mold steel not having high thermal conductivity.
[0011] Although the prior art has provided various improved hot working die steels, there is still a need for hot working die steels with high thermal conductivity, high hardness and high toughness.
[0012] Summary of the Invention
[0013] The present invention is made in view of the above-mentioned problems existing in the prior art. One object is to provide a hot work die steel that can achieve better thermal conductivity and mechanical properties through a simple hardening process. The chemical composition of the hot work die steel is as follows, by weight percentage: Ni: 4.5-12%, Al: 0.8-2.1% (with Al: Ni = 0.075-0.234), Cu: 0.4-1.99%, Mn: 0.001-1%, C: 0.0001-0.1%, with the balance being Fe and unavoidable impurities.
[0014] Preferably, Al:Ni is greater than or equal to 0.075 and less than 0.18.
[0015] Preferably, Al:Ni is greater than or equal to 0.18 and less than or equal to 0.234.
[0016] More preferably, Al:Ni is greater than or equal to 0.18 and less than or equal to 0.22, and Ni is 5 to 9%.
[0017] Preferably, C: 0.0001 to 0.05%.
[0018] The material composition of hot work die steel is designed with the understanding that after appropriate heat treatment, all alloying elements precipitate from the matrix in the form of Cu particles and Ni(Fe, Al) intermetallic compounds. In particular, Al continues to precipitate as intermetallic compounds with Ni after hardening, reducing matrix lattice defects and improving thermal conductivity. In this application, when the Al content dissolved in the matrix is ≤ 0.05%, all Al is considered to have precipitated from the matrix. Because these precipitates inherently possess excellent thermal conductivity, they not only ensure high hardness and toughness but also enhance the thermal conductivity of the hot work die steel.
[0019] Preferably, the material composition of hot work die steel should also be designed to improve its aging resistance. Research has shown that by setting the Cu:Al ratio to 0.5 < 1, preferably, 0.4-1.5% Cu, this can improve the aging resistance of hot work die steel. More preferably, the Cu:Al ratio is 0.6-0.9, and even more preferably, the Cu ratio is 0.4-1.2%.
[0020] Preferably, the chemical composition of the hot working die steel of the present invention is, by weight percentage, as follows: Ni: 5-12%, Al: 0.8-1.5% and 0.075≤Al:Ni<0.18, Cu: 0.4-1.0% and 0.5<Cu:Al<0.9, Mn: 0.001-1%, C: 0.0001-0.1%, and the balance is Fe and unavoidable impurities.
[0021] Preferably, the chemical composition of the hot work die steel of the present invention is, by weight percentage, as follows: Ni: 5.5-11%, Al: 1.2-2.1% and 0.18≤Al:Ni≤0.234, Cu: 1.0-1.9% and 0.8<Cu:Al<1, Mn: 0.001-1%, C: 0.0001-0.1%, with the balance being Fe and unavoidable impurities. Preferably, the chemical composition of the hot work die steel of the present invention is, by weight percentage, as follows: Ni: 5.5-7.0%, Al: 1.0-1.6% and Al:Ni=0.18-0.20, Cu: 0.4-1.0% and 0.5<Cu:Al<0.9, Mn: 0.001-1%, C: 0.0001-0.1%, with the balance being Fe and unavoidable impurities. Preferably, the chemical composition of the hot working die steel of the present invention is, by weight percentage, as follows: Ni: 7.5-9%, Al: 1.2-2.1% and Al:Ni=0.20-0.234, Cu: 1.0-1.9% and 0.8<Cu:Al<1, Mn: 0.001-1%, C: 0.0001-0.1%, and the balance is Fe and unavoidable impurities.
[0022] Another object of the present invention is to provide a heat treatment method for the above-mentioned hot working die steel, which is carried out on existing heat treatment and processing equipment, which not only simplifies the current die steel heat treatment process to reduce costs, but also enables the hot working die to have better mechanical properties and thermal conductivity.
[0023] The heat treatment method of the present invention comprises a hardening treatment step, wherein:
[0024] When 0.4% ≤ Cu < 0.8%, the hot work die steel is heated to a temperature in the range of 560-650°C; when 0.8% ≤ Cu < 1.5%, the hot work die steel is heated to a temperature in the range of 470-580°C; and when 1.5% ≤ Cu ≤ 1.99%, the hot work die steel is heated to a temperature in the range of 450-520°C; maintained for 1-240 hours, preferably 4-24 hours, and then cooled to room temperature.
[0025] On the one hand, the precipitated Cu particles will coarsen as the Cu content and temperature increase, which in turn will cause the coarsening of the NiAl precipitation phase; on the other hand, the precipitated Cu particles serve as nucleation sites to promote the precipitation of NiAl. At the same temperature, the lower the Cu content, the smaller the size of the Cu precipitate phase, which can avoid coarsening. However, too low a Cu content is not easy to promote NiAl precipitation. Both aspects will change the performance of the mold steel. Therefore, the present invention coordinates the Cu content and the hardening temperature, that is, determines the hardening temperature based on the Cu content, so that during the hardening process, the synergistic effect of the Cu content and temperature not only promotes the precipitation of Cu particles and NiAl, but also avoids the coarsening phenomenon.
[0026] Preferably, when 0.4%≤Cu<0.8%, the hot work die steel is heated to a temperature in the range of 560-620°C; when 0.8%≤Cu<1.5%, the hot work die steel is heated to a temperature in the range of 480-580°C; and when 1.5%≤Cu≤1.99%, the hot work die steel is heated to a temperature in the range of 450-500°C.
[0027] After hardening treatment, the properties of the hot work die steel are as follows: hardness ≥36HRC, room temperature thermal conductivity: 34~50W / mK, impact energy of unnotched specimen (7×10×55mm) ≥200J, and Al dissolved in the matrix ≤0.05%.
[0028] Preferably, before the hardening treatment step, a solution treatment step is performed: the hot working die steel is heated to 850-950° C. and maintained for 0.5-240 hours, and then cooled to room temperature.
[0029] Preferably, before the solution treatment step, a forging step is performed: the hot working die steel is heated to 900-1150°C for forging, and then cooled to room temperature. Preferably, the forging temperature is 950-1100°C, more preferably 1000-1050°C.
[0030] Preferably, the cooling in the solution treatment and / or forging step is first slowly cooled to below 600°C, preferably below 500°C, more preferably below 400°C at a rate of ≤60°C / h, preferably ≤30°C / h, and then air-cooled to room temperature.
[0031] The heat treatment method of the present invention eliminates the spheroidizing annealing process of the current die steel due to the use of the steel of the present invention, and the solution treatment temperature is reduced from 1000-1050°C to 850-950°C, reducing the requirements for heat treatment equipment. In addition, the hardening process is carried out at a single temperature for a long time. This is because the steel claimed to be protected by this application does not contain elements that can form other alloy carbides, so if carbides appear, they can only be cementite. Since the carbon content of the present invention is low, carbides are not easy to grow. Therefore, the present application can perform long-term hardening treatment at a single temperature, making the hardening process simple and avoiding the current hardening treatment process of hot working die steel that requires continuous heat preservation at different temperatures for different times.
[0032] Yet another object of the present invention is to provide a hot working die made of the hot working die steel that has undergone the above-mentioned heat treatment, which has high hardness, high thermal conductivity and high toughness. Preferably, the die is resistant to high temperature ripening (i.e., the precipitated phase is not easy to grow at high temperature), so that the performance of the hot working die does not deteriorate during service, thereby improving the thermal fatigue resistance of the die. In addition, the hot working die according to the present application has high thermal conductivity, so it can shorten the production cycle time and improve production efficiency. Preferably, the hot working die can be a steel plate hot stamping die, an aluminum alloy die-casting die, or a hot extrusion drawing hot working die.
[0033] The descriptions of the chemical element contents (%) herein all refer to weight percentages. Unless otherwise specified, the preferred embodiments can be freely combined as needed.
[0034] In addition, it will be understood by those skilled in the art that any range or any specific value within the above-mentioned respective ranges is applicable to the present invention. For example, 0.075-0.18 (excluding 0.18) includes any subrange and any specific value therein, such as any value of 0.075, 0.08, 0.082, 0.085, 0.088, 0.09, 0.095, 0.1, 0.13, 0.15, 0.157, 0.16, 0.165, 0.17, 0.175, and any range of 0.075-0.085, 0.08-0.098, 0.09-0.14, 0.12-0.17. Similarly, 0.18-0.234 includes any sub-range and any specific numerical value therein, such as any numerical value such as 0.18, 0.185, 0.19, 0.195, 0.198, 0.203, 0.207, 0.213, 0.215, 0.225, and any range such as 0.18-0.215, 0.18-0.207, 0.185-0.225, 0.19-0.225, 0.19-0.22. Similarly, 0.5 to 1 (excluding the end values) includes any subrange and any specific numerical value therein, such as any numerical value of 0.56, 0.62, 0.69, 0.73, 0.80, 0.88, 0.90, 0.92, 0.98, and any range of 0.51 to 0.98, 0.56 to 0.92, 0.62 to 0.98, 0.65 to 0.92, 0.65 to 0.9, etc. Unless explicitly stated, all ranges include the end values. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] FIG1 is a micrograph of Example S3 after hardening treatment (580° C. for 12 hours). DETAILED DESCRIPTION
[0036] The present invention will be described in more detail below with reference to exemplary embodiments.
[0037] The chemical composition of the hot-working die steel according to the present invention is, by weight, 4.5-12% Ni, 0.8-2.1% Al (where Al:Ni = 0.075-0.234), 0.4-1.99% Cu, 0.001-1% Mn, and 0.0001-0.1% C. The balance is Fe and unavoidable impurities. The functions and proportions of the various elements in the present invention are described below.
[0038] Ni: The main role of nickel in the present invention is to form NiAl intermetallic compounds, which play a role in precipitation strengthening and hardening. In addition, Ni can inhibit the generation of liquid phase of Cu at the grain boundary under high temperature, which leads to the occurrence of thermal cracking of the alloy during high-temperature deformation, thereby ensuring the hot forming performance of the alloy. The alloying element Ni can improve the hardenability of steel, inhibit bainite transformation, and Ni enriched at the grain boundary can improve toughness. When it is expected that the steel will use the precipitated intermetallic compound NiAl as the main strengthening and hardening phase, it must contain a higher content of nickel, otherwise the Al element cannot be fully combined with Ni to precipitate from the matrix, causing the Al element to be solid dissolved in the matrix. This will seriously reduce the thermal conductivity of the steel. Under the condition of ensuring that Al is completely precipitated, excessive Ni solid dissolved in the matrix will not cause obvious lattice distortion, but when Ni is excessive, M s The temperature is too low, so that during the cooling process, austenite does not transform into martensite, which causes cracking due to its own large thermal expansion coefficient. In order to ensure the complete precipitation of Al and prevent Ni from causing low M s Temperature, the nickel content of the steel of the present invention is between 4.5% and 12%. Preferably, the nickel content is 5% to 12%, more preferably, the nickel content is 5% to 11%, and even more preferably, the nickel content is 5% to 9%. First, nickel ensures that aluminum is completely precipitated from the matrix, meeting the performance requirements of the present invention; second, excessive nickel does not improve performance, but instead increases alloy cost; finally, excessive nickel may increase machining difficulties (for example, "tool sticking" during turning).
[0039] Al: Aluminum and nickel can form NiAl intermetallic compounds during the hardening process at 400-650°C, which plays a role in precipitation strengthening and hardening. In addition, the precipitation of NiAl intermetallic compounds improves the purity of the matrix. At the same time, NiAl intermetallic compounds also have good thermal conductivity (~90W / mK), both of which improve the thermal conductivity of steel. In order to ensure that Al is completely precipitated from the matrix in the form of NiAl intermetallic compounds, excessive Al relative to the Ni content will cause the following problems: 1. Al cannot be completely precipitated from the matrix, thereby reducing the thermal conductivity of the steel; 2. It is easy to form large AlN inclusions, which will not be fully dissolved in austenite at high temperatures, thereby seriously damaging the toughness of the steel; 3. Al, as a strong ferrite stabilizing element, will increase the A c1 and A c3Temperature, when solution treatment is required, austenitization must be achieved at a higher temperature, thereby increasing manufacturing costs, increasing energy consumption burden and raising requirements for heat treatment equipment. When the Al content is low, complete precipitation of Al can be guaranteed. However, the hardness of the steel does not meet the use requirements due to the inability to precipitate enough NiAl intermetallic compounds. In addition, insufficient Al due to excessive Ni elements will not have a significant impact on the hardness, thermal conductivity and impact energy of the present invention, but will only cause a waste of Ni elements and increase material costs. Therefore, the aluminum content of the steel of the present invention is between 0.8 and 2.1%, and Al:Ni=0.075~0.234, preferably, 0.18~0.234, and further preferably 0.18~0.22. At this time, the ratio of Ni and Al elements is optimal and the effect is optimal.
[0040] Cu: Pure copper is a good conductor of heat, with a thermal conductivity of 398 W / mK, compared to only 80 W / mK for pure iron. Cu has a high solubility in the face-centered cubic phase (austenite) but a low solubility in the body-centered cubic phase (ferrite and / or martensite), allowing the precipitation of copper particles. The precipitated ε-Cu particles range in size from 3 to 10 nm. Adding 1% Cu by weight can increase the matrix hardness by approximately 100 HV. Cu precipitates from the body-centered cubic matrix (ferrite and / or martensite), reducing the distortion of the matrix crystal structure. Combined with the high thermal conductivity of the precipitated Cu particles, they can improve the thermal conductivity of the matrix. However, the precipitated Cu particles have a low ripening temperature. When the matrix temperature rises (for example, during hardening), the Cu particles grow rapidly, resulting in a decrease in the hardness and strength of the steel. In addition, during the hot forming of steel (such as rolling, forging, etc.), Cu easily forms liquid Cu at the grain boundaries of austenite, causing hot cracks in the steel during deformation, reducing the plastic deformation ability of the steel and making it impossible to process. In order to inhibit the liquid precipitation of Cu at the grain boundaries, a certain weight fraction of the alloying element Ni is usually added. The precipitated Cu particles can provide nucleation sites for the precipitation of NiAl intermetallic compounds, thereby promoting the precipitation of intermetallic compounds NiAl. Taking into account the effect of Cu and the Al content of the present invention, the copper content of the steel of the present invention is between 0.4 and 1.99%, and in order to improve the aging performance, it is preferably specified that the weight ratio of Cu to Al is 0.5 to 1 (excluding the end value), and further preferably, the weight ratio of Cu to Al is 0.6 to 0.99, and / or the Cu content is 0.4 to 1.2%.
[0041] Mn: Manganese is an austenite-forming element that delays the transformation of austenite to ferrite, which is beneficial for refining ferrite grains and improving the strength and toughness of steel. Mn dissolved in the matrix will reduce the thermal conductivity of steel. When Mn replaces part of Fe and Al atoms to form Ni (Fe, Mn, Al) intermetallic compounds, the thermal conductivity of the original Ni (Fe, Al) will be reduced. Moreover, when the Mn content is too high, on the one hand, austenite will remain in the steel, resulting in uneven structure and unstable steel performance; on the other hand, NiMn precipitates will form at the grain boundaries, seriously damaging the mechanical properties of the steel. Therefore, the present invention limits the Mn content to between 0.001 and 1%.
[0042] C: One of the most effective and economical strengthening elements in steel, it is an austenite stabilizing element. Carbon is an interstitial solid solution element, and its strengthening effect is far greater than that of substitutional solid solution elements. Carbon can improve the hardenability of steel, and the cementite or alloy carbide formed significantly increases the hardness of the alloy. When the C content increases, network carbides and coarse cementite will form along the grain boundaries, seriously reducing the toughness of the steel. Since the present invention is based on NiAl and Cu precipitation strengthening and does not rely on the strengthening and hardening of carbides, the carbon content of the steel of the present invention is between 0.0001 and 0.1%.
[0043] The following examples and experimental data are intended to illustrate the present invention. It should be clear to those skilled in the art that the present invention is not limited to these examples or experimental data.
[0044] According to the present invention, there is provided a first preferred hot working die steel comprising the following composition by weight: Ni: 4.5-5.5%, Al: 0.8-1.3% with Al:Ni=0.075-0.234, Cu: 0.4-1.99% with 0.6≤Cu:Al≤0.99, Mn: 0.001-1%, C: 0.0001-0.1%, and the balance being Fe and unavoidable impurities.
[0045] According to the present invention, there is provided a second preferred hot working die steel comprising the following composition by weight: Ni: 5.5-7.5%, Al: 1.0-1.6% with Al:Ni=0.075-0.234, Cu: 1.0-1.5% with 0.5<Cu:Al<1, Mn: 0.001-1%, C: 0.0001-0.1%, and the balance being Fe and unavoidable impurities.
[0046] According to the present invention, there is provided a third preferred hot working die steel comprising the following composition by weight: Ni: 7.5-12%, Al: 1.2-2.1% with Al:Ni=0.075-0.234, Cu: 1.5-1.99% with 0.5<Cu:Al<1, Mn: 0.001-1%, C: 0.0001-0.1%, and the balance being Fe and unavoidable impurities.
[0047] According to the compositions of the exemplary steels DC1 to DC8 and the comparative steels CG1 to CG3 shown in Table 1, the steel ingots were smelted and forged at about 1050°C and finished at about 950°C to obtain 80×80 mm 2 Afterwards, the billet was homogenized at 1030°C for 5 hours and then air-cooled to room temperature.
[0048] Table 1 Composition of the example steel of the present invention and the comparative steel (weight percentage, wt%)
[0049] Steel numberNiAlCuCMnFeAl:NiCu:AlDC14.50.90.60.0090.005Bal.0.200.67DC25.61.21.00.0020.08Bal.0.210.83DC3 6.51.21.00.050.1Bal.0.180.83DC48.51.81.70.010.5Bal.0.210.94DC56.51.20.50.010.5Bal.0.180.42DC67 .51.50.50.0050.1Bal.0.20.33DC74.51.01.60.010.006Bal.0.221.6DC8100.90.60.0090.005Bal.0.090.67CG 16.52.01.50.060.09Bal.0.310.75CG28.70.61.00.0020.08Bal.0.0691.67CG37.520.840.050.1Bal.0.270.42
[0050] The billet was cut into samples of 7.2×10×55 mm and φ12.7×2.2 mm, and heat treated using the heat treatment method of the present invention. The heat treatment method of the present invention comprises the following steps:
[0051] Under laboratory conditions, the steel was first solution treated at 950°C for one hour, followed by quenching to room temperature. The steel was then hardened at a temperature between 450°C and 650°C for a predetermined time, followed by air cooling to room temperature. The solution treatment and hardening treatment parameters for the sample and comparison steels are shown in Table 2.
[0052] It will be understood that the temperature and duration of the hardening treatment process described above are not limited to the specific temperatures and durations described in the embodiment, but can be selected within the following ranges: when 0.4% ≤ Cu < 0.8%, the hot work die steel is heated to a temperature within the range of 560-650°C; when 0.8% ≤ Cu < 1.5%, the hot work die steel is heated to a temperature within the range of 470-580°C; and when 1.5% ≤ Cu ≤ 1.99%, the hot work die steel is heated to a temperature within the range of 450-520°C. The heat treatment method of the present invention may optionally include other treatment processes, such as forging. Furthermore, the temperature and duration of the solution treatment and / or forging processes can be selected according to actual needs.
[0053] Table 2 Parameters for solution treatment and hardening treatment of example steel and comparison steel
[0054]
[0055] Hardness measurement: After the solution treatment and hardening treatment samples were polished to a bright finish with sandpaper, hardness tests were performed using a hardness tester (Rockwell hardness) to obtain the hardness values H of the solution treatment samples. S And the hardness value H after hardening H , see Table 3.
[0056] Impact energy measurement: The 7.2 × 10 × 55 mm specimens heat treated according to Table 2 were mechanically polished into 7 × 10 × 55 mm unnotched impact specimens according to the North American Die Casting Association's unnotched impact specimen standard. The specimens were then subjected to a 450 J pendulum unnotched room temperature impact test to obtain the impact energy of the specimens, as shown in Table 3.
[0057] Al Content Measurement: Micro-area Al content analysis was performed using energy-dispersive X-ray spectroscopy (EDX-ray spectroscopy) on 7.2 × 10 × 55 mm specimens heat-treated according to Table 2. Composition analysis was performed at least five locations on each specimen. The Al content in the matrix was determined by averaging the Al content at each location. The results are shown in Table 3.
[0058] Thermal conductivity measurement: Thermal conductivity λ = α × c p ×ρ×100, the unit of thermal diffusion coefficient α is cm 2 / s, specific heat capacity c p The unit of is J / (gK), the unit of density is g / (cm 3), the unit of direct calculation is W / (cmK)×100, and the unit obtained is W / (mK). The φ12.7×2.2mm cylindrical sample heat-treated according to Table 2 was ground into a φ12.7×2.0mm sample with 1000-grit sandpaper, and then the thermal conductivity was measured on a DLF2800 flash thermal conductivity meter. The measurement process is: increase the temperature to 100℃ at a rate of 5K / min at 25℃, stabilize at 100℃ for an estimated 10 minutes, and then perform the first measurement; then continue to stabilize for 10 minutes and perform the second test; and then stabilize for another 10 minutes and perform the third measurement. After that, increase the temperature to 200℃ at a rate of 5K / min and measure three times according to the above process. Then increase the temperature to 300℃, 400℃ and 500℃ in turn and measure three times according to the above process (equivalent to keeping warm for 30 minutes at each measurement temperature). After the measurement is completed, the sample is cooled to room temperature. The thermal diffusivity and specific heat capacity data at each temperature are obtained based on the measurement. The thermal conductivity is then calculated from the thermal diffusivity, specific heat capacity and density, see Table 4.
[0059] Aging Test: Aging refers to the phenomenon in which the strengthening effect of the secondary phase in steel decreases due to the coarsening of the secondary phase at different holding temperatures and times. The degree of aging can be expressed as the percentage reduction in hardness. For Examples S4 and S7, after the solution treatment process described in Table 2, the following hardening treatment was performed: After holding at 520°C for 4 hours, 24 hours, and 48 hours, the hardness was measured according to the aforementioned measurement method, and the percentage reduction in hardness was calculated. See Table 5.
[0060] Table 3 Hardness value, impact energy and Al content in matrix of each sample of the present invention
[0061]
[0062] Table 4 Thermal conductivity of each sample of the present invention, W / (mK)
[0063] Temperature / ℃25100200300400500DC1S136.237.138.640.239.237.9DC2S240.242.443.545.344.542.9DC3S342.944.245.747.648.147.2DC4S444.347.649.150.249.448.2DC5S543.745.246.948.247.145.9DC6S645.146.347.948.549.147.6DC7S737.538.440.641. 540.338.8DC8S836.237.238.640.239.237.9DC1CS129.129.831.132.329.428.2DC3CS243.244.445.647.546.344.7DC4CS344.8 46.948.850.149.348.2CG1CS425.827.128.630.229.127.7CG2CS542.743.64546.243.843.1CG3CS627.629.330.431.330.528.9
[0064] Table 5 Hardness of Examples S4 and S7 of the present invention after aging test
[0065]
[0066] Hardness analysis
[0067] The hardness values of Examples S1-S8 and Comparative Examples CS1-CS6 after solution treatment are all lower than 35HRC. This is because the precipitated phases (such as NiAl and Cu) in the microstructure are dissolved in the matrix through solution treatment and no longer play a role in strengthening and hardening.
[0068] After hardening treatment, the hardness values of Examples S1-S8 and Comparative Examples CS1-CS6 increased, and compared with the hardness value H after solution treatment, S , the hardness value H of the hardened examples S1-S8 H The hardness of the steel samples S1-S8 and CS1-CS6 increased by 24% to 51.3%, reaching over 36 HRC. In contrast, the hardness of the steel samples CS1-CS6 increased by only 16.2% after hardening, reaching between 33.4 and 35.2 HRC, which does not meet the requirements for use. This increase in hardness is due to the precipitation of NiAl intermetallic compounds and Cu particles during the hardening process in both Examples S1-S8 and Comparative Examples CS1-CS6. These compounds strengthen and harden the steel, thereby improving its strength and hardness to a certain extent.
[0069] Compared with Example S1, Example S8 has a higher Ni content, making Al:Ni 0.09. After undergoing the same heat treatment process as Example S1, the measured H H Although slightly lower than S1, it still meets the technical effect of the present invention. Therefore, it can be seen that a moderate excess of Ni does not lead to a significant decrease in hardness.
[0070] Similarly, Example S2 and Comparative Example CS5 also reflect the influence of excessive Ni element. After Example S2 and Comparative Example CS5 were subjected to the same heat treatment process, the solution treated hardness H of Example S2 was S The hardness is 31.8HRC and the hardness is H H It is 47.5HRC, which is higher than H S 49.3% higher. S is 31.8HRC, and H H is 34.1HRC, which is higher than H S It is only 6.7% higher. This is because compared with Example S2, the Al content of Comparative Example CS5 is less than the Ni content, and the Ni content is much excessive (Al:Ni is only 0.069). Although all Al can form NiAl intermetallic compounds with Ni to precipitate (microscopic analysis found that the Al content in the matrix of Comparative Example CS5 is 0.03%), the precipitated NiAl intermetallic compounds are limited, so the strengthening and hardening effects of the NiAl intermetallic compounds are also limited. In addition, since the Ni element is a substitutional solid solution element, the solid solution strengthening effect is very weak, that is, the improvement of the hardness by the solid solution Ni is very limited. These two aspects lead to the obtained H H The Al content is too low to meet the requirements of use. In addition, the low Al content relative to the Ni content will result in the excessive Ni element failing to achieve the strengthening and hardening effect, resulting in waste. Based on this, in order to precipitate sufficient NiAl intermetallic compounds, it is expected that the Al:Ni ratio is at least greater than 0.069.
[0071] The present invention has found that when the Ni element is so high that the Al:Ni ratio is less than 0.075 (such as in comparative example CS5), the desired steel performance cannot be achieved. Therefore, in order to achieve the technical effect of the present invention, the Al:Ni ratio must be at least not less than 0.075.
[0072] After the same heat treatment process as Example S3 and Comparative Example CS6, the H H The HRC of comparative example CS6 is 42.3. HIt is 34.6HRC, which is about 18% lower than Example S3. This is because compared with Example S3, the Al content of Comparative Example CS6 is too much relative to the Ni content, so that Al cannot be completely precipitated from the matrix, resulting in less NiAl precipitation phase, and thus weak strengthening and hardening effect, which ultimately leads to its hardness failing to meet the use requirements. Microscopic analysis found that the Al content in the matrix of Comparative Example CS6 was 0.25%, which also confirmed that Al failed to completely precipitate from the matrix. Compared with CS6, the hardness of Comparative Example CS4 is lower. Microscopic analysis found that the Al content in the matrix of Comparative Example CS4 (Al:Ni is 0.31) was 1.14%, indicating that more Al failed to precipitate from the matrix, making the final hardness unable to meet the use requirements. Based on the above, in order to completely precipitate Al, it is expected that Al:Ni is at least less than 0.27.
[0073] The Al:Ni ratio of Examples S1-S8 is within the range of 0.075 to 0.234. Microscopic analysis of Examples S1-S8 after heat treatment revealed that the Al content in the matrix of Examples S1-S8 was less than 0.05%, and Ni(Fe, Al), Ni(Fe, Mn, Al) and Cu particles were precipitated in the matrix, as shown in Figure 1. These results indicate that the Al:Ni ratio within the range of 0.075 to 0.234 ensures that Al can be completely precipitated from the matrix in the form of NiAl intermetallic compounds, and that sufficient precipitates can play a role in precipitation strengthening and hardening, resulting in a hardness value of H 1000 after hardening treatment. H Reach 36HRC or above.
[0074] As can be seen from the above, while meeting the steel's elemental composition ranges, maintaining an Al:Ni ratio within the range of 0.075-0.234 ensures the desired high hardness of the steel. Preferably, the Ni:Al ratio is 0.18-0.234, more preferably 0.18-0.22, and even more preferably, the Ni content is 5-9%. In preferred cases, lower Ni content achieves equivalent or even higher performance.
[0075] Impact energy
[0076] The impact energies of Examples S1 to S8 are all greater than 200 J, and the corresponding hardness values (not less than 36 HRC) also meet the requirements for use. This is because, for Examples S1 to S8, the Cu and NiAl precipitations not only strengthen the steel but also prevent the interface with the substrate from becoming a favorable location for crack initiation and propagation, thus achieving both high toughness greater than 200 J and high hardness of not less than 36 HRC.
[0077] In contrast, the impact energy of comparative example CS6 is only 189J and the hardness is only 34.6HRC, which means that both hardness and toughness do not meet the requirements. Although the impact energy of comparative examples CS1 to CS5 exceeds 200J, the corresponding hardness values are less than 36HRC, which cannot meet the requirements of high hardness and high toughness at the same time.
[0078] Thermal conductivity
[0079] The calculated thermal conductivities of Examples S1-S8 and Comparative Examples CS1-CS6 at various test temperatures are listed in Table 4.
[0080] The thermal conductivity of Examples S1-S8 is greater than 36 W / mK in the range of 25-500°C. In particular, at 300°C, the thermal conductivity of Examples S1-S8 exceeds 40 W / mK, and the thermal conductivity of Examples S2-S6 even reaches above 45 W / mK.
[0081] Since the comparison results of the thermal conductivity of each sample are similar at various temperatures, the following discussion only takes the thermal conductivity at 300°C as an example:
[0082] Examples S1 and S8 differ only in Ni content, and the thermal conductivities obtained under the same heat treatment process are similar. This shows that when Ni is excessive within a certain degree relative to Al content, it will not lead to a significant change in thermal conductivity.
[0083] The thermal conductivity of Comparative Examples CS4 and CS6 (Al:Ni ratios of 0.31 and 0.27, respectively) is lower than that of all Examples S1-S8, at only 30.2 W / mK and 31.3 W / mK, respectively. This is because after hardening, approximately 1.14% and 0.25% of Al remain dissolved in the matrix of Comparative Examples CS4 and CS6, respectively, causing severe lattice distortion and reducing thermal conductivity. Comparative Examples CS4 and CS6 lack both high hardness and high thermal conductivity.
[0084] Comparative Example CS5 has a significantly higher thermal conductivity than CS4 and CS6. This is because the Al in Comparative Example CS5 (Al:Ni ratio of 0.069) is completely precipitated from the matrix, and excess Ni (relative to the Al content) does not significantly affect the thermal conductivity of the steel (see Examples S1 and S8). However, as mentioned above, due to the limited amount of precipitated NiAl intermetallic compounds, the resulting hardness is relatively low and does not meet the requirements for use. Comparative Example CS5 cannot achieve both high hardness and high thermal conductivity.
[0085] From the above, it can be seen that, first, the failure of Al to precipitate completely from the matrix will significantly reduce the thermal conductivity of the matrix. Combining the hardness and thermal conductivity data of each sample, it can be seen that high thermal conductivity can be obtained by ensuring that Al is completely precipitated from the matrix during the hardening process. Second, excessive Ni elements will not have a significant effect on thermal conductivity. Therefore, while ensuring that Al is completely precipitated from the matrix and sufficient precipitates are precipitated, the Ni content can be adjusted as desired. When both high thermal conductivity and high hardness are required, it is necessary to control Al:Ni within the range of 0.075 to 0.234, which ensures that Al is completely precipitated from the matrix in the form of NiAl intermetallic compounds, and that there are sufficient precipitates to play a role in precipitation strengthening and hardening, so that the hardness value H after hardening treatment is 1.547 W / cm2. H Reaching HRC above 36 and thermal conductivity above 36 W / mK. Preferably, the Ni:Al ratio is 0.18 to 0.234, more preferably the Ni content is 5 to 9%, and more preferably the Ni:Al ratio is 0.18 to 0.22. Compared to a Ni:Al ratio of 0.075 or greater and less than 0.18, a Ni:Al ratio of 0.18 to 0.22 achieves comparable thermal conductivity at a relatively low Ni content, saving Ni content, reducing costs, and minimizing the likelihood of machining difficulties.
[0086] Hardening treatment
[0087] In order to ensure that the steel has the desired hardness and thermal conductivity, the choice of hardening temperature is also crucial when the Al:Ni ratio is in the range of 0.075 to 0.234. For example, the comparative example CS1 has the same composition as the example S1 (wherein Al:Ni = 0.20; Cu content is 0.6%), but is kept at a lower temperature (460°C) during the hardening process. On the one hand, the lower hardening temperature leads to insufficient Cu precipitation, which in turn cannot effectively promote the precipitation of NiAl. On the other hand, the lower hardening temperature cannot provide sufficient thermodynamic driving force for NiAl to promote its precipitation. The combined effect of the two results in insufficient NiAl precipitation, resulting in the matrix of the comparative example CS1 still containing about 0.21% Al after hardening. On the one hand, this leads to limited hardening effect, resulting in low hardness of the obtained steel; on the other hand, the Al in the matrix causes lattice distortion, which significantly reduces the thermal conductivity, such as only 32.3W / mK at 300°C.
[0088] Comparative Example CS2 has the same composition as Example S3 (Al:Ni = 0.18; Cu content is 1.0%), but is held at a higher temperature (620°C) during the hardening process. The high temperature promotes the precipitation and rapid coarsening of Cu, which in turn promotes the precipitation and coarsening of NiAl. Although Al precipitation is complete (the Al content in the matrix of Comparative Example CS2 is 0.02%), the coarsening of Cu particles and NiAl precipitates reduces the strengthening and hardening effect, resulting in a significantly lower hardness of Comparative Example CS2 than Example S3.
[0089] Comparative Example CS3 has the same composition as Example S4 (where Al:Ni = 0.21; Cu content is 1.7%), but is held at a higher temperature (650°C) during the hardening process. The higher Cu content and higher hardening temperature both promote the precipitation of Cu particles and their coarsening at high temperatures. While this promotes the complete precipitation of Al as NiAl precipitates (the Al content in the matrix of Comparative Example CS3 is 0.02%), it also causes the NiAl precipitates to coarsen, reducing their strengthening and hardening effects, thereby reducing the hardness of Comparative Example CS3. H Only 33.6HRC.
[0090] Note that Comparative Examples CS2 and CS3 have relatively high thermal conductivities of 47 W / mK and 50 W / mK, respectively. This is because, for both, Al is completely precipitated from the matrix. On the one hand, the coarsening of the Cu particles and the NiAl precipitate phase does not result in a change in thermal conductivity. On the other hand, the high temperature also significantly recovers the dislocations in the material matrix, improving the thermal conductivity of the matrix. However, as mentioned above, due to the excessively high hardening temperature, the hardness of both has dropped to below 35 HRC, which is unsatisfactory for use. Comparative Examples CS2 and CS3 cannot achieve both high hardness and high thermal conductivity.
[0091] As can be seen from the above, in the case of the composition range and the ratio between the elements of the die steel meeting the application, the selection of unreasonable hardening temperature will cause steel to have high hardness and high thermal conductivity concurrently. In conjunction with the data of each embodiment and comparative example, in the case of low Cu content, the Cu particle of separating out can only promote the precipitation of NiAl to a limited extent. In this case, for NiAl to separate out fully from matrix, need higher hardening temperature to separate out large thermodynamic driving force for NiAl, to obtain high hardness (referring to embodiment S3 and S5). Equally, in the case of high Cu content, the Cu particle of separating out can well promote the precipitation of NiAl. At this moment, in order to ensure precipitation strengthening and hardening effect, should adopt lower hardening temperature to prevent Cu particle and NiAl precipitate coarsening (referring to embodiment S4).
[0092] Therefore, in order to ensure that the steel has the desired hardness and thermal conductivity, it is necessary to select an appropriate hardening temperature based on the Cu range, so as to promote the precipitation of NiAl intermetallic compounds through Cu while preventing the precipitated Cu particles and NiAl intermetallic compounds from coarsening during the hardening process. According to experimental data, when 0.4% ≤ Cu < 0.8%, the hardening temperature is in the range of 560-650°C; when 0.8% ≤ Cu < 1.5%, the hardening temperature is in the range of 470-580°C; when 1.5% ≤ Cu ≤ 1.99%, the hardening temperature is in the range of 450-520°C.
[0093] Combining the above experimental results, it can be seen that, while meeting the range of the steel's various elemental composition, by keeping the Al:Ni ratio within the range of 0.075 to 0.234 and selecting an appropriate hardening temperature, a steel with high hardness, high toughness, and high thermal conductivity can be obtained. The main reasons are summarized as follows:
[0094] 1. As a ferrophilic alloying element, Ni will not reduce the thermal conductivity of the iron matrix when it is dissolved in an appropriate amount in the iron matrix;
[0095] 2. During the hardening process, the Al element will combine with the Ni element to form a NiAl intermetallic compound, whose chemical formula is Ni(Fe, Al). The solid solution of the Al element in the matrix will seriously reduce the thermal conductivity of the matrix and fail to achieve the expected hardening effect. By ensuring that the Al:Ni ratio is within the range of 0.075 to 0.234, it is ensured that the Al element can be completely precipitated from the iron matrix after hardening. Furthermore, an appropriate increase in the Ni content will not significantly improve or deteriorate the technical effects of the present invention, such as hardness, impact energy and thermal conductivity, so preferably, Al:Ni is 0.18 to 0.234 and Ni: 4.5 to 11%. Further preferably, Al:Ni is 0.18 to 0.22 and Ni: 5 to 9%. The preferred solution achieves the same or even better technical effects under conditions of lower Ni content;
[0096] 3. Cu precipitation provides nucleation sites for NiAl precipitation, thereby promoting the precipitation of NiAl. Therefore, the precipitation of NiAl can be promoted by adjusting the Cu content;
[0097] 4. Since both the nucleation and growth of NiAl and Cu require a large driving force, by selecting a suitable hardening temperature in the range of 450-650°C according to the Cu content, it is possible to promote the precipitation of the precipitated phase while ensuring that the precipitated phase is not excessively coarsened, thereby ensuring that the hardness and thermal conductivity meet the use requirements. For example, in Example S6 with a low Cu content, by utilizing a high hardening temperature to provide a large thermodynamic driving force for NiAl precipitation, the complete precipitation of the NiAl intermetallic compound is promoted without relying on the precipitation of Cu, thereby ensuring hardness and thermal conductivity;
[0098] 5. The high thermal conductivity Ni(Fe, Al) precipitation phase, the high thermal conductivity Cu precipitation phase and the clean matrix all contribute to the high thermal conductivity of the steel of the present invention.
[0099] Ripening analysis
[0100] As shown in Table 5, for Example S7 (where Cu:Al is 1.6), the hardening temperature selected is 520°C according to its Cu content. When the hardening time is 4 hours, the hardness value H H As the hardening time is extended to 24 hours and 48 hours, H H The steel is significantly reduced in temperature, with the degree of ripening being 16.3% and 24.8%, respectively. Cu has a lower precipitation temperature than NiAl, making it more susceptible to ripening. When the Cu:Al ratio is greater than 1, a large number of Cu particles coarsen, which also causes NiAl to coarsen. The coarsening of the second-phase Cu and NiAl particles leads to ripening of the steel.
[0101] In contrast, for Example S4 (where Cu:Al is 0.94), the hardness value H obtained after hardening is 4 hours. H 50.2HRC. Although with the extension of hardening time H H decreased, but the H obtained after 48 hours of hardening H Still very high (45.7HRC), meet the use requirements, and the aging phenomenon is not obvious. Example S4 has good aging resistance because: on the one hand, the present invention reduces the Cu content to 0.4~1.99% (as S4 and S7, Al is 1.7% and 1.6% respectively) on the whole, and selects appropriate hardening temperature according to the Cu content, which prevents the Cu particles from precipitating from growing up quickly and then promotes the NiAl of precipitating to grow up quickly. On the other hand, by controlling the Cu:Al ratio within the range of 0.5~1 (excluding end values), the NiAl precipitated phase and the Cu particles limit their aging process each other, so that even under long-term hardening treatment, the aging degree is controlled within 10%, effectively improving the aging resistance of the steel.
[0102] In summary, the hot work die steel of the present invention is capable of fully precipitating alloying elements dissolved in the matrix during hardening, particularly Al, from the matrix. Precipitates such as Cu particles and NiAl intermetallic compounds not only provide excellent thermal conductivity but also enhance the steel's strength, thereby increasing both its thermal conductivity and hardness after hardening. Furthermore, the hot work die steel of the present invention features a simple production process, reducing manufacturing costs and enabling its manufacture using existing heat treatment and processing equipment.
[0103] The hot working die of the present invention can be used for steel plate hot stamping forming dies, aluminum alloy die casting, hot extrusion drawing hot working dies, etc.
[0104] The above embodiments and experimental data are intended to illustrate the present invention by way of example. It should be clear to those skilled in the art that the present invention is not limited to these embodiments, and various modifications may be made without departing from the scope of protection of the present invention.
Claims
1. A hot working die steel, wherein the chemical composition thereof is, by weight percentage, as follows: Ni: 4.5-12%, Al: 0.8-2.1% (with Al:Ni=0.075-0.234), Cu: 0.4-1.99%, Mn: 0.001-1%, C: 0.0001-0.1%, and the balance being Fe and unavoidable impurities.
2. The hot working die steel according to claim 1, wherein: 0.075≤Al:Ni<0.
18.
3. The hot working die steel according to claim 1, wherein: 0.18≤Al:Ni≤0.
234.
4. The hot working die steel according to claim 3, wherein: 0.18≤Al: Ni≤0.22 and Ni: 5 to 9%.
5. The hot working die steel according to any one of claims 1 to 4, wherein: 0.5<Cu:Al<1 and / or Cu: 0.4~1.5%.
6. The hot working die steel according to claim 5, wherein: 0.6≤Cu:Al≤0.9 and / or Cu:0.4~1.2%.
7. The hot working die steel according to any one of claims 1 to 4 and 6, wherein: C:0.0001~0.05%。 8. A heat treatment method for hot working die steel according to any one of claims 1 to 7, comprising a hardening treatment step: when 0.4 ≤ Cu < 0.8%, heating the hot working die steel to a temperature within the range of 560 to 650° C.; when 0.8 ≤ Cu < 1.5%, heating the hot working die steel to a temperature within the range of 470 to 580° C.; when 1.5 ≤ Cu ≤ 1.99%, heating the hot working die steel to a temperature within the range of 450 to 520° C. and maintaining the temperature for 1 to 240 hours, and then cooling the hot working die steel to room temperature.
9. The heat treatment method according to claim 8, comprising: When 0.4%≤Cu<0.8%, heat the hot working die steel to a temperature within the range of 560~620℃; When 0.8%≤Cu<1.5%, the hot work die steel is heated to a temperature in the range of 480~580℃; and when 1.5%≤Cu≤1.99%, the hot work die steel is heated to a temperature in the range of 450~500℃ and maintained for 4~24 hours, and then cooled to room temperature.
10. The heat treatment method according to claim 8 or 9, further comprising: Before the hardening step, a solution treatment step is performed: the hot working die steel is heated to a temperature in the range of 850 to 950° C. and maintained for 0.5 to 240 hours, and then cooled to room temperature.
11. The heat treatment method according to claim 10, further comprising: Before the solution treatment step, a forging treatment step is performed: the hot working die steel is heated to a temperature within a range of 900 to 1150° C. for forging, and then cooled to room temperature.
12. The heat treatment method according to claim 10 or 11, wherein The cooling in the solution treatment step and / or the forging step is firstly slowly cooled to below 600° C. at a rate of ≤60° C. / h, and then air-cooled to room temperature.
13. The heat treatment method according to claim 8 or 9, wherein The properties of the heat-treated hot working die steel are as follows: hardness ≥36HRC, room temperature thermal conductivity: 34~50W / mK, impact energy of unnotched specimen ≥200J, and Al dissolved in the matrix ≤0.05%.
14. A hot working die made of hot working die steel obtained by the heat treatment method according to any one of claims 8 to 13, characterized in that: Hot working dies can be used as steel plate hot stamping dies, aluminum alloy die casting dies, or hot extrusion and drawing hot working dies.